L’ attirail d’un magicien rangé dans une cave de Chartres/Autricum - Dominique Joly; Richard Gordon; Jonathan Simon; William Van Andringa; Stéphane Willerval (Gallia)
An incense burner, bearing a magical inscription in Latin and snake potteries were found by chance at Chartres in July 2005. The emergency excavation which followed revealed an assemblage of objects linked to magical practices. These objects were hidden in the tiny cellar of a domus collapsed after a fire at the turn of the 1st and 2nd century AD.This set includes three snake-vases, a broad-bladed knife, two oil lamps, fifteen entire vessels (bottles, flasks, plates and jars), a small assortment of carbonised animal bones and smelt glass sherds. Iron and copper-alloy pieces and bone hinges make possible the reconstruction of a casket, a cupboard and probably one or two chests.The text of the turibulum is inscribed from the top to the foot, on four columns divided by vertical lines, each one corresponding to a cardinal direction. It’s an invocation to the omnipotentia numina for their custos and one of the few beneficial magical texts discovered in the Roman world, which mentions a Roman citizen of the Carnutum civitas, C. Verius Sedatus. He probably comes from this civitas and is presumably the magician or he may be the only commissioner of the ceremony. This study gives the opportunity to identify the equipment of a magician which consists on one hand of items produced for magical rites and on the other hand of household utensils, changed for a ritual purpose.